Realizacja przez administrację publiczną odpowiedzialności w ochronie środowiska - Maciej Jabłoński (Studia Ecologiae et Bioethicae)
Environmental protection is an area of interdisciplinary, in which the rule is the use of concepts relevant to the legal sciences, natural sciences, engineering, or chemical. Therefore, in practice, they may mean different things depending on the conceptual context in which they are used. The concept, which draws attention to the rights and duties of citizens, public authorities, or environmental organizations, is a responsibility in protecting the environment. The state authorities should support citizens in their efforts to protect and improve the environment. Ecological safety, which is to be provided by a public authority is a state of the environment that allows you to safely stay in it and use it. The instrument to ensure that safety is the protection of the environment, which acts as a directive interpretation when there are doubts as to the scope of duties, such duties, and how they are implemented.